Sistem Pendukung Keputusan Pemilihan Kapten Tim Futsal Dengan Metode Analytical Hierarchy Process (AHP) - Dwi Handoko (Jurnal Ilmiah Informatika dan Ilmu Komputer (JIMA-ILKOM), 2022)
The selection of the futsal team captain is an important step in building a solid and successful team. The purpose of the research conducted to determine the captain of the futsal team using the AHP method as a support for the coach's decision in determining who will be the captain of the futsal team. The calculation of the selection of the futsal team captain using AHP rank 1 was obtained by Pras with a value of 0.22921 being the highest among other futsal team captain candidates. With the application of this AHP method, Pras recommended to be the captain of the futsal team.